2014
DOI: 10.3389/fcimb.2014.00116
|View full text |Cite
|
Sign up to set email alerts
|

Immunity-related genes in Ixodes scapularis—perspectives from genome information

Abstract: Ixodes scapularis, commonly known as the deer tick, transmits a wide array of human and animal pathogens including Borrelia burgdorferi. Despite substantial advances in our understanding of immunity in model arthropods, including other disease vectors, precisely how I. scapularis immunity functions and influences persistence of invading pathogens remains largely unknown. This review provides a comprehensive analysis of the recently sequenced I. scapularis genome for the occurrence of immune-related genes and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 132 publications
1
89
0
Order By: Relevance
“…During the acquisition and transmission blood meals, B. burgdorferi, an extreme auxotroph, must adapt physiologically to the fed midgut milieu, particularly with respect to the use of alternate carbon sources (12)(13)(14). Spirochetes also must cross physical barriers (i.e., peritrophic and basement membranes) and evade the tick's innate immune defenses, which includes antimicrobial peptides and defensins, lysozyme, agglutinins/lectins, complement-related molecules, and reactive oxygen species (ROS) (4,(7)(8)(9)(10)(11). In order to migrate into and out of the vector, Borrelia must sense and respond to chemotactic signals encountered within the bite site and midgut, respectively (113,114).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the acquisition and transmission blood meals, B. burgdorferi, an extreme auxotroph, must adapt physiologically to the fed midgut milieu, particularly with respect to the use of alternate carbon sources (12)(13)(14). Spirochetes also must cross physical barriers (i.e., peritrophic and basement membranes) and evade the tick's innate immune defenses, which includes antimicrobial peptides and defensins, lysozyme, agglutinins/lectins, complement-related molecules, and reactive oxygen species (ROS) (4,(7)(8)(9)(10)(11). In order to migrate into and out of the vector, Borrelia must sense and respond to chemotactic signals encountered within the bite site and midgut, respectively (113,114).…”
Section: Discussionmentioning
confidence: 99%
“…Successful colonization of the vector requires B. burgdorferi to establish an intimate association with rapidly differentiating, highly endocytic midgut epithelial cells (4)(5)(6). In order to accomplish this feat, spirochetes must resist deleterious substances within the midgut lumen, such as host-and tick-derived innate immune effector molecules, reactive oxygen species (ROS), and salivary enzymes imbibed from the feeding site (4,(7)(8)(9)(10)(11). At the same time, B. burgdorferi also must alter its metabolic machinery to exploit the availability of alternative carbon sources (e.g., glycerol, N-acetylglucosamine [GlcNAc], chitobiose) as the supply of ingested glucose diminishes (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…A visible PM is shown to be formed around 6-12 hours after tick feeding [80], so are the luminal bacteria in brief contact with the epithelial cells during the pre-PM formation stage? If they are, then the immunome of the tick gut [81, 82] must respond to this contact and the resulting immune milieu must influence the ability of the incoming pathogens to colonize the tick. The microbiome composition might determine the potency of the immune response, potentially detrimental to incoming pathogens.…”
Section: The Spatial Organizationmentioning
confidence: 99%
“…In tick research, some LRR-containing proteins have been identified from Ixodes scapularis (Smith and Pal 2014); however, their functions are still unknown. Unlike in ticks, the roles of LRR-containing proteins from other arthropods are relatively well understood, especially in the mosquitoes as reviewed by Cirimotich et al (2010).…”
Section: Introductionmentioning
confidence: 99%